Vitamin C Use among the Public: Findings from a Cross-sectional Survey in Malaysia - Md Nasir, Muhammad Syafiq; Jamal, Janattul Ain; Abd Wahab, Mohd Shahezwan (Media Gizi Indonesia, 2026)
Vitamin C supplements are widely used for their perceived benefits on immunity, collagen synthesis, and overall health. However, limited research has explored their usage prevalence and associated sociodemographic factors among the public. This study aims to examine the patterns of vitamin C supplement use, factors associated with its use, and the reasons for non-use among Malaysian adults. A cross-sectional survey was conducted from March to April 2024 among 408 Malaysian adults, recruited via convenience sampling. Data were collected through a self-administered online questionnaire, which captured demographic characteristics, vitamin C supplement usage patterns, reasons for use or non-use, sources of information and healthcare consultation behaviour. Descriptive statistics were used to summarize the data, and chi-square or Fisher’s exact tests were applied to identify associations between demographic variables and vitamin C supplement use. Vitamin C supplement use was reported by 79.2% of respondents, with higher prevalence among females, married individuals, and those aged ≥ 30 years. Key motivations included maintaining health (82.4%) and boosting immunity (84.8%). Pharmacies were the primary source (73.1%), while social media dominated as an information channel. Healthcare professional consultation was low, with only 26.9% consulting doctors and 47.7% consulting pharmacists. Non-users primarily cited preferences for natural sources (55.3%) and adequate dietary intake (29.4%) as reasons for non-use. Vitamin C supplement use is widespread in Malaysia, but low engagement with healthcare professionals and high reliance on non-professional sources suggest a need for targeted education and professional guidance to ensure safe and informed supplementation practices.